COMPLEMENTATION OF H-2-LINKED IR GENES - USE OF HELPER FACTOR TO ANALYZE RESPONSES TO GLYPHE - Baltz, M; Maurer, P; Merryman, C; Feldmann, M (Springer-Verlag, 1978)
Responses to GLPhe5 were generated in vitro, using the GLPhe helper factor. A plaque assay, using GLPhe-coated SRC, was used to measure antibody responses to GLPhe. Mice of different H-2 haplotypes were tested for the ability to produce the GLPhe helper factor or to respond to a known GLPhe helper factor. We report here defects in nonresponder mice of different strains in both the production of helper factor and in the capacity to respond to it. © 1978 Springer-Verlag New York Inc.